Analisis Dampak dan Kesadaran Masyarakat terkait Administrasi Kependudukan melalui Program Kalimasada Kelurahan Gunung Anyar - R. Yuniardi Rusdianto; Savira Maslihatul Mamlu’ah (Institut Teknologi dan Bisnis Semarang, 2023)
The KALIMASADA (Population Administration Aware Community Neighborhood Area) program aims to make the public aware of the importance of population administration in their daily lives, with a focus on having complete and accurate population documents such as KTP, KK, and birth certificates.In line with this goal, a study was conducted by UPN Veterans East Java students through the Ministry of Education and Culture's MBKM Internship. This study aims to analyze the impact and awareness of the community regarding population administration through the Kalimasada Program in Gunung Anyar Village. This program is designed to increase public awareness about the importance of population administration and having complete population documents. The data collection method used in this study was the collection of KK (Family Cards) data directly on the people involved in the Kalimasada Program. The results showed that the Kalimasada Program in Gunung Anyar Village had a positive impact on public awareness regarding population administration. Through socialization activities, assistance, and population administration services provided by this program, people are becoming more aware of the importance of having complete population documents, such as National Identity Cards (KTP), Family Cards (KK), and birth certificates